Prevalence of digestive diseases in patients with excessive body weight and obesity (according to data of polyclinic department of versatile clinic) - I. R. Popova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study prevalence of digestive diseases in patients with excessive body weight and obesity.Material and methods. Retrospective study of diseases of digestive organs prevalence included 1504 patients, who have visited polyclinic department in 2010 : 659 with excessive body weight – body mass index (BMI) 25,0 to 29,9 kg/m2), 610 with obesity (BMI ≥30 кг/м2) and 235 with normal weight (BMI 18,5 to 24,9 kg/m2), the latter made control group. All patients were investigated in polyclinic department and Vasilenko Clinic of internal diseases propedeutics, gastroenterology and hepatology, University clinical hospital #2, State educational government-financed institution of higher professional education Sechenov First Moscow state medical university of the Russian federation Ministry of Health and Social Development.Results. Every third patient who has visited polyclinic department, had excessive body weight (34,4%), every fourth (25,3 %) was obese. Of diseases of digestive organs the most frequent were: non-alcoholic fatty liver disease (NAFLD) – 83,4 % (r=0,35, p<0,001), non-alcoholic steatohepatitis (NASH) – 13,1% (r=0,14, p<0,001), gallstone disease (GSD) – 41,8 % (r=0,05, p <0,05); steatosis of the pancreas – 86,4% (r=0,20, р<0,001). The rate of patients with insulin resistance (IR) at obesity was 61,3%.Conclusion. The prevalence of liver steatosis in obesity was 2,7 times, and in NASH – 8 times higher, than in patients with normal BMI. Frequency of GSD, steatosis of the pancreas at obesity was 2-fold higher over the scores of normal BMI group. IR was found in 60% of patients with obesity, that in 4 times higher, than in control group (15,2%). The obesity is modifiable risk factor and application of the respective measures of prophylaxis will promote decreased progression of digestive diseases.